Plan de negocios para la creación y comercialización de una revista digital para la Universidad Técnica de Cotopaxi, extensión La Maná año 2012 - Ruales Burbano, Cristian Andrés (2014)
The research is presented because of the lack of production of digital magazines at the Technical University of Cotopaxi and in La Maná canton. This study aims to determine the profitability of a digital magazine production company which is not only located in the canton but also based on a Technical, Financial, and Market Study. The project was based on surveys that were applied to people who will consume the product. According to this, it provided valuable criteria in order to assist as a support for the implementation of a Production Company of digital magazines....